Levels and patterns of material deprivation in Ireland: After the Celtic Tiger - Christopher T. Whelan; Bertrand Maître (The Economic and Social Research Institute (ESRI), 2005)
In this paper we use the first full wave of the Irish component of the EU Statistics on Income and Living Conditions survey to evaluate conflicting interpretations of levels and patterns of material deprivation in Ireland after the Celtic Tiger. Radical critics of Irish economic policies have seen the Irish case as a particularly good illustration of the tendency for globalization to be accompanied by widespread economic vulnerability and marginalization. Such arguments, however, have focused unduly on relative income poverty measures. Here, employing a multidimensional perspective that encompasses not only income but also a range of deprivation dimensions, we adopt a tiered approach to the analysis of economic vulnerability and multiple deprivation. Our analysis identifies one fifth of the population as being economically vulnerable. A sub-group constituting one half of this economically vulnerable cluster is identified as 'consistently poor'. Finally, seven per cent of the population are identified as maximally deprived in that they exhibit high risks of deprivation across a range of life-style deprivation dimensions. Both the levels and depth of material deprivation are a good deal more modest than suggested by radical critics of the recent Irish experience.
Keywords: 330